PERANCANGAN KEBUTUHAN TENAGA KERJA OPERATOR PRODUKSI DI PT XYZ - Silitonga, Jaka Putra Iman Kristian; Citra Indah Asmarawati (LPPM Universitas Putera Batam, 2024)
Broadly speaking,all work done by humans is divided into two categories, namely the category of work that uses mental and physical where both categories are very influential in the work to be done, PT. XYZ is a company engaged in hardisk, the many demands given to employees cause mental felt by the employees themselves, Nasa TLX this method is divided into six main factors. From this study, the researchers found out the level of mental workload and felt by operators